Development and Role of Measurement Tools in Educational Evaluation - Fitriani, Namiyah; Sintya Rahmadewi; Nurhadi; Shuhada (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2025)
Evaluation in education and learning is essential for assessing student competencies, measuring teaching effectiveness, and ensuring continuous educational improvement. This study explores the development of measurement tools and their role in enhancing learning quality. Using a qualitative approach with a library research method, data collection is conducted through an in-depth review of academic literature, including books, journal articles, research reports, and educational policy documents. The study follows four stages: (1) identifying and selecting credible literature sources, (2) categorizing information based on key evaluation concepts, (3) conducting theoretical comparisons to identify similarities and differences, and (4) synthesizing findings to develop a comprehensive understanding of evaluation in education. The findings highlight the significance of valid and reliable measurement tools in accurately assessing learning outcomes. Effective evaluation not only measures student achievement but also functions as a feedback mechanism for educators, enabling them to refine teaching methods and curriculum design. Additionally, the study emphasizes that a well-structured evaluation system contributes to institutional development by promoting accountability, improving instructional strategies, and supporting evidence-based decision-making in education. To ensure the reliability of findings, the research applies a multi-source approach, comparing diverse academic references to validate information. The study concludes that an effective and structured evaluation process is vital for optimizing educational outcomes, fostering student success, and enhancing overall teaching quality. Recommendations for future research include expanding the scope of evaluation methods and integrating technology-based assessment tools for more accurate and comprehensive learning evaluations.